Security Council and General Assembly Reformation: Responding Human Rights Issues - Iradhati Zahra (PADJADJARAN LAW RESEARCH AND DEBATE SOCIETY, 2019)
Abstract The United Nations nowadays has many problems. By looking some case, especially human rights issues, the resolutions that the United Nations establish or about to establish is barely done. All of these matters started from the authority that the Security Council and the General Assembly as the State-Representative Organs have. Especially, the authority of the P5 members (China, United States, Russia, United Kingdom, and France), which is the veto power. This implementation of veto power has been implemented in the case of Rohingya. Even though this crisis of human rights in Rohingya is important, the political importance of some states are still prevailing the crisis of human rights in Rohingya. For example, it happened when China had vetoed this issue, which almost submitted to the ICC. Refered to those statements, this article propose two solutions to responding human rights issues. First, the United Nations has an urgency to reform the organization by modification the authority of the General Assembly and the Security Council, mainly in the system of establishing the resolutions. Second, the solution is to make a short-term period program in refining the human rights issues, and to improve the commitment of the United Nations for maintaining international peace and security as it written in the purposes of the UN Charter. Keywords: Security Council, General Assembly, reformation, human rights, authority Abstrak Perserikatan Bangsa – Bangsa pada dewasa kini memiliki banyak permasalahan. Dengan melihat beberapa kasus yang terjadi, terutama yang berkaitan dengan isu hak asasi manusia, resolusi – resolusi yang dikeluarkan atau hendak dikeluarkan oleh Perserikatan Bangsa – Bangsa jarang terselesaikan dengan baik. Seluruh permasalahan ini diawali dari kewenangan yang dimiliki oleh Majelis Umum PBB dan Dewan Keamanan PBB sebagai organ perwakilan negara – negara. Terutama, keewenangan yang dimiliki oleh anggota P5 atau anggota tetap Dewan Keamanan PBB (Cina, Amerika Serikat, Russia, Inggris, dan Perancis), yaitu hak veto. Implementasi dari hak veto ini telah dilaksanakan pada kasus rohingya. Walapun, kasus krisis hak asasi manusia di Rohingnya ini sangat penting, kepentingan politik dari beberapa negara masih dapat mengungguli urgensi dari krisis hak asasi manusia yang terjadi di Rohingya. Sebagai contoh,hal ini terjadi ketika Cina menggunakan hak vetonya pada isu Rohingya ketika isu ini hampir dibawa ke ICC. Berdasarkan pernyataan tersebut, artikel ini menggagas dua solusi dalam merespon isu hak asasi manusia. Pertama, PBB memiliki urgensi untuk mereformasi organisasi ini dengan memodifikasi kewenangan Majelis Umum dan Dewan Keamanan, terutama dalam sistem penerbitan resolusi. Kedua, yaitu dengan membuat program jangka pendek dalam melakukan pemulihan hak asasi manusia, dan untuk memperbaiki komitmen PBB dalam menjaga perdamaian dan keamanan internasional sebagaimana yang tercantum sebagai tujuan di Piagam PBB. Kata Kunci: Dewan Keamanan, Majelis Umum, reformasi, Hak Asasi Manusia, Kewenangan